Upaya Perlindungan Terhadap Hak Narapidana Kategori Lanjut Usia - Prakoso, Dewo Tegar; Subroto, Mitro (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2021)
In correctional institutions, the number of cases of elderly prisoners is still quite a lot. In fact, even the elderly can violate the law. In serving the sentence of inmates with the status of the elderly, it is necessary to protect their rights because of the decline in the cycle of human life. The Ministry of Law and Human Rights of the Republic of Indonesia has taken an action to base reference on international standards for special treatment for elderly prisoners. The release of prisoners' rights should be carried out in every correctional institution because the elderly are included in the category of vulnerable group prisoners who require special attention. The discussion in this article is useful for explaining the implementation of services and protection of rights that belong to elderly prisoners. This article is descriptive. Through the discussion presented, it is hoped that it can become a basis in the form of scientific studies in order to build a global commitment to the fulfillment and enforcement of human rights in prisons